TO THE SYNTHESIS OF A LAYOUT OF MACHINE TOOL FOR BATCH PROCESSING - B. M. Rozin; V. E. Zdanovich (Informatika)
The problems of choosing the optimal standard size of the basic units and assembly components of machine tools for batch processing of parts are considered. The algorithms for solving some of these problems by optimizing of mutual disposition of unit elements are proposed. The algorithm for constructing 3D-models of machine tool layout elements in the graphics system T-Flex is pro-posed. The structure and method for implementation of the software for construction and estimation of the machine tool layouts for batch processing are given.